Image and Presence of the Medieval Sacramental Liturgy in The Redemption Triptych of the Prado Museum - Pazos-López, Ángel (Eikón / Imago, 2017)
This paper studies the genesis of iconographic programs of sacramental themes between the 14th and 15th centuries, with special focus on the pictorial program of the Redemption Triptych of the Prado Museum. The sacraments, as sensitive signs that help the faithful to reach salvation, are paced with the milestones of the Christian’s life. Taking into account the ritual and the theological traditions of the sacraments in the Late Middle Ages, the Redemption Triptych is related to other compositions that combine sacramental practices and the Passion of Christ, as a basis for achieving the Christian idea of salvation. Finally, the meaning of the ritual signs embodied in the liturgical scenes present in the work of the Prado Museum will be explained, putting them in relating them to sources and liturgical or paraliturgical practices of the time.